Populating the handbook on governance statistics with empiraical evidence : illustrations from GPS-SHaSA survey modules in Africa - (:unkn) unknown (My University, 2019)
The 2030 Agenda and the transition from the MDGs to the SDGs focus on the quality of institutions,governance, peace and security (GPS). This renewed interest drove a pressing need for measurement,monitoring and evaluation in developing countries and rich countries. Such are the aims of SDG16 at globallevel and Agenda 2063 (Aspirations 3 and 4) in Africa. This working paper describes and analyses eightdimensions of governance drawn from GPS-SHaSA initiative household surveys “Governance, Peace andSecurity” in nine Sub-Saharan African countries. Those dimensions are: Non-discrimination and equality;Participation in political and public affairs; Openness; Access to and quality of justice; Responsivenessand satisfaction with services; Absence of corruption; Trust in institutions; Safety and security. Thisdocument helps populating with empirical evidence the UN Handbook on governance statistics,developed under the auspices of the Praia Group on Governance Statistics.
Keywords: African Research